PACIENTES CON ENFERMEDAD RENAL CRONICA ESTADIO IV CURSANDO CON DEPRESION EN EL SERVICIO DE UROLOGIA DEL HOSPITAL REGIONAL DE ICA DURANTE EL PERIODO 2021 - CHAVARRIA SANCHEZ, ROSA MARGARITA (2021)
Objective: To determine patients with stage IV chronic kidney disease suffering from depression in the urology service of the Regional Hospital of Ica during the period 2021. Material and methods: Non-experimental: since they are not being modified or an attempt is made to modify the study variables through interventions. Cross-sectional: The collection of information will be in a single time and the patients will not be followed throughout their treatment. Descriptive: The phenomena found will be detailed. Population: The total significant sample is 125 patients with chronic kidney disease on dialysis at the Ica Regional Hospital, with a safety level of 99%. The sample of the present study is probabilistic, specifically the type of sampling is random by conglomerates, a number of patients who attended the urology service of the Regional Hospital of Ica were randomly selected, day by day until the total sample was reached. Results: In the results obtained, the pathologies that led our population to dialysis were not taken into account. Likewise, a relationship was found between dialysis time, the presence of symptoms and their severity; the shorter the dialysis time, the more severe the depressive symptoms. Conclusions: The prevalence of depression in patients with terminal chronic kidney disease treated in the dialysis unit of the Regional Hospital of Ica is greater than half of the cases and affects mostly female patients. Keywords: Chronic Kidney Disease, Dialysis, Depression.